Stunting Reduction: TTS District Community Empowerment Based on Local Wisdom (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Stunting has become a serious problem today. Data shows that East Nusa Tenggara (NTT) Province first ranks in stunting nationally. Based on the 2021 Indonesian Nutritional Status Study (SSGI), 15 districts in NTT are categorized as red (stunting prevalence >30%). South Middle East (TTS) and North Middle East (TTU) districts have a prevalence of >46%. This study aims to discuss the model of community empowerment in dealing with stunting which has become a serious problem today in South Middle East District (TTS). The method used is direct education (a method that involves delivering information and knowledge directly to individuals or groups). The results show that community empowerment to reduce stunting is a collective work between pentahelix elements, community empowerment programs in Haumenbaki Village rely on the strength of local wisdom, namely manonop (cooperation) and three important actors of community empowerment elements in Haumenbaki Village, namely the community, village government, and external institutions (agencies, universities, NGOs, and the media).